Campo Baeza (Massachussets : Rockport, 1997)
Viviendas, arquitectura educacional, edificios públicos
Keywords: ARQUITECTOS; ARQUITECTURA CONTEMPORANEA; SIGLO XX; CAMPO BAEZA, ALBERTO; VIVIENDA; EDIFICIOS PUBLICOS; ARQUITECTURA EDUCACIONAL; ESPAÑA